Identity and acculturation: The case for Africa. Issue 2 (24th April 2017) - Adams, Byron G.; van de Vijver, Fons J. R.
Abstract : Despite the multicultural nature of African societies, there is still very little knowledge about acculturation and its association with identity on this continent. Acculturation processes and outcomes are strongly associated with identity. The objective of this article is to relate different models of acculturation (unidimensional, bi-dimensional, multidimensional) with the tri-dimensional model of identity (personal, relational, and social). Social identity components, such as ethnicity, religion, and culture, suggest a need for modification of Western models of acculturation to embrace the multifaceted realities of non-Western multicultural societies. The social complexity and the continuous transition within African societies provides unique opportunities to examine and further develop the multidimensional acculturation models to take into account the social complexity which informs identity issues both within and across different African nations.